Fingerprinting Northeast Atlantic water masses using neodymium isotopes. (1st August 2017) - Dubois-Dauphin, Quentin; Colin, Christophe; Bonneau, Lucile; Montagna, Paolo; Wu, Qiong; Van Rooij, David; Reverdin, Gilles; Douville, Eric; Thil, François; Waldner, Astrid; Frank, Norbert
Abstract: Dissolved neodymium (Nd) isotopic composition (expressed as εNd) has been analysed for 82 seawater samples collected from 13 stations stretching from the Alboran Sea to the Iceland Basin. The distribution of the εNd values of water masses was thus investigated for the first time along the western European margin in order to explore whether the water masses flowing in the eastern subpolar and subtropical Atlantic reveal distinct isotopic patterns. The Modified Atlantic Water (MAW) in the Alboran Sea displays εNd values (between −9.2 ± 0.2 and −8.9 ± 0.2) that are significantly more radiogenic than those reported in previous studies (−10.8 ± 0.2 to −9.7 ± 0.2), suggesting temporal variations in the Nd isotopic composition of the water that enters the Mediterranean Sea from the Strait of Gibraltar. The εNd value of the underlying modified Winter Intermediate Water (WIW) has been established for the first time (−9.8 ± 0.3) and is compatible with a Nd signature acquired from the sinking of MAW in the northwestern Mediterranean Sea. Within the Gulf of Cádiz, southern Mediterranean Sea Water (MSW) (−10.6 ± 0.2) differs slightly from the northern MSW (−9.9 ± 0.4) owing to a significant contribution of modified East Antarctic Intermediate Water (EAAIW) (−10.9 ± 0.2). In the northeast Atlantic, the North Atlantic Current surface water located in the inter-gyre region (north of 46°N) displays εNd values of between −14.0 ± 0.3 and −15.1 ± 0.3, reflecting the subpolar gyre signature. Along the western European margin, εNd values of surface water decrease toward the north (from −10.4 ± 1.6 to −13.7 ± 1.0) in agreement with the gradual mixing between subtropical and subpolar water. At intermediate depth, εNd values decrease from −9.9 ± 0.4 within the Gulf of Cádiz to −12.1 ± 0.2 within the Porcupine Seabight, indicating a strong dilution of the MSW with subpolar water. Within the Rockall Trough and the Iceland Basin, the more negative εNd values at mid-depth (<−13.5 ± 0.3) indicate that the MSW has no influence, even during periods of low NAO index. Water masses deeper than 1200 m in the northeast Atlantic are clearly influenced by the less radiogenic Labrador Sea Water (LSW) (εNd between −13.4 ± 0.3 and −14.0 ± 0.3) that mixes locally in the Iceland basin with the Iceland-Scotland Overflow Water (ISOW) (between −10.3 ± 0.2 and −11.3 ± 0.3).